2010
DOI: 10.1007/s10661-010-1666-2
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of nested spatial patterns and seasonal variation in the longitudinal distribution of Sicyopterus japonicus in the Datuan Stream, Taiwan by using geostatistical methods

Abstract: This study attempts to determine the scale-dependent hierarchical spatial variation and longitudinal distributions of Sicyopterus japonicus year round. The distribution of S. japonicus in the Datuan Stream in northern Taiwan was surveyed during the fall and winter 2007, as well as the spring and summer of 2008. The spatial structure of S. japonicus density was modeled using geostatistics. The longitudinal distributions of S. japonicus density were then estimated using kriging and hydrology distance with nested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…Consistent with previous studies, Sicyopterus japonicas, an amphidromous gobiid, was the focal species, as it has often been identified as a habitat quality indicator species [5,[31][32][33]. [5,32] have described the study area and the method for collecting data in more detail. Figure 1 presents the study area and sampling locations as well as the number of Sicyopterus japonicas observed.…”
Section: Methodssupporting
confidence: 56%
See 2 more Smart Citations
“…Consistent with previous studies, Sicyopterus japonicas, an amphidromous gobiid, was the focal species, as it has often been identified as a habitat quality indicator species [5,[31][32][33]. [5,32] have described the study area and the method for collecting data in more detail. Figure 1 presents the study area and sampling locations as well as the number of Sicyopterus japonicas observed.…”
Section: Methodssupporting
confidence: 56%
“…V and D were classified using the classification criterion that was proposed by [32]. Both the projected current velocity and water depth across the study area were inputted into the species distribution models.…”
Section: Hydraulic Model and Model Unitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the total length of Datuan Stream is 14.5 km and the watershed covers 15.68 km 2 , with an average slope of 7.5%. Additionally, it is the third largest stream within Tamsui District and is managed at the national level [54]. Datuan Watershed maintains a subtropical monsoon climate with northeastern and northern monsoons in the winter, and southeastern and eastern monsoons in the summer.…”
Section: Research Areamentioning
confidence: 99%
“…Kriging is an interpolation procedure widely used to analyse the spatial behaviour for a given variable in many of the natural sciences, including geology (Mendes and Ribeiro, 2010;Pérez-Rodríguez et al, 2007), zoology (Lin et al, 2011), botany (Fortin et al, 1989), ecology (Robertson, 1987), and climatology (Bajat et al, 2013). Over the last few years, a number of papers have addressed the use of geostatistical techniques coupled with GIS in phenological and aerobiological researches (e.g.…”
Section: Introductionmentioning
confidence: 99%